Constructive Learning Models on Students' Understanding and Application of Learning Concepts - Subaedah; Wahab, Abdul; Azhar, Muh; Sudarmono, Muh Aidil; Zainal, Abdul Qahar (Tafkir: Interdisciplinary Journal of Islamic Education, 2023)
This study aims to determine the differences between the constructivist learning model and the conventional learning model for 1) the ability to understand and apply science concepts; 2) interest in learning science; and 3) scientific performance in the field of science. Using a quasi-experimental research learning model with independent variables constructivist learning models and conventional learning models, and the dependent variable includes the ability to understand and apply science concepts, interest in learning science, and scientific performance in science. The population in this study were students of SMP Negeri 34 Makassar, as a sample of students in class VII2 and class VII5 who were randomly selected. The results of the descriptive analysis showed that there was a significant difference in scientific performance between the class with the constructivist learning model and the control class with the conventional learning model. The experimental class obtained a mean = 85.94, the control class obtained a mean = 66.09. The results of the data analysis concluded that there were significant differences in the ability to understand and apply science concepts, interest in learning science, and scientific performance in science between students who were given a constructivist learning model and students who were given a conventional learning model.